Analisis Efektivitas: Pengumpulan dan Pendistribusian Dana Zakat oleh BAZNAS Pekanbaru dalam Pemberdayaan Masyarakat - Sartika Alusna; Erica Sasmita; Susila Wati (CV. KAMPUSA AKADEMIK PUBLISHING, 2025)
This study aims to analyze the effectiveness of zakat collection and distribution by BAZNAS Pekanbaru in the context of community empowerment. The research employed a qualitative descriptive approach by analyzing both primary and secondary data. The findings indicate that zakat collection realization only reached 26.7% of its potential, constrained by insufficient outreach and lack of technological utilization. In terms of distribution, empowerment programs have benefited recipients; however, their impact remains unsustainable due to limited guidance and evaluation. This study recommends enhancing technology-based strategies, strengthening stakeholder collaboration, and involving communities to improve the effectiveness of zakat management in Pekanbaru.